Digital curation fundamentals - DeRidder, Jody L., 1957- (Rowman & Littlefield, 2018)
"Digital Curation Fundamentals takes a straight-forward, commonsense approach to the complex problem of digital curation and preservation, and portrays the challenges and opportunities in an approachable conversational style which lowers the bar to include those with little to no technical expertise"--